2014
DOI: 10.1111/ijn.12275
|View full text |Cite
|
Sign up to set email alerts
|

Care demands on mothers caring for a child with Down syndrome: Malaysian (Sarawak) mothers' perspectives

Abstract: This paper examines the experiences of mothers caring for a child with Down syndrome in the Malaysian (Sarawak) context. Qualitative interviews were conducted with 26 biological mothers of children with Down syndrome aged 18 years and below. They were accessed through selected child health clinics, community-based rehabilitation centres and schools using purposive sampling within two regions in Sarawak, one of the two Borneo States of Malaysia. Major themes emerging within the context of care demands were chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 33 publications
0
8
0
11
Order By: Relevance
“…Girls with Down syndrome could not use pads at all, they could only stare at blood stains on pants. 19 Respondents strongly agree that they feel happy when children with Down syndrome could speak a few words that are understandable by anyone. Many mothers of children with Down syndrome feel very happy when their children could speak a few words that are understandable by anyone.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Girls with Down syndrome could not use pads at all, they could only stare at blood stains on pants. 19 Respondents strongly agree that they feel happy when children with Down syndrome could speak a few words that are understandable by anyone. Many mothers of children with Down syndrome feel very happy when their children could speak a few words that are understandable by anyone.…”
Section: Resultsmentioning
confidence: 99%
“…In a qualitative study, it had been found that there was a Chinese mother trying to increase learning potential of her child that born with Down syndrome, as her child experienced delay in learning. 19 In addition to perceived maternal responsiveness style in children with Down syndrome, it was also found in respondents answers which still applied perceived parenting demandingness. Perceived parenting demandingness is a perception that describes standards set by parents are related to parental control of child's behavior.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A interação pais 1 -criança assume fundamental importância especialmente na primeira infância, período que compreende dos 0 aos 6 anos (Arpini et al, 2015;Seidlde-Moura et al, 2004;Wendland, 2001). Esse investimento inicial, por vezes, é dificultado frente à descoberta de um diagnóstico de deficiência (Chan et al, 2015;Dezoti et al, 2015). Em função disso, o cuidado de crianças com deficiência pode ser acompanhado de alto nível de estresse parental (Chan et al, 2015;Goff et al, 2016;Smith et al, 2014), o que torna o suporte social fundamental nesse contexto (Dezoti et al, 2015; Grisante e Aiello, 2012; Yamashiro e Matsukura, 2014).…”
Section: Introductionunclassified